TINJAUAN MAQASHID SYARIAH TERHADAP PERMENHUB NOMOR PM 25 TAHUN 2020 TENTANG PENGENDALIAN TRANSPORTASI SELAMA MASA MUDIK IDUL FITRI 1441 H DALAM RANGKA PENCEGAHAN PENYEBARAB COVID-19 - Sesah, Meria Deran; Junaidi, Heri; Armasito, Armasito (Muamalah, 2021)
ABSTRACT Research with the title Maqashid Syariah review of PERMENHUB Number PM 25of 2020 concerning Transportation Control during the Eid Al-Fitr Homecoming Period 1441H in the Context of Preventing the Spread of Covid-19. Starting from the spread of CoronaVirus Disease 2019 (Covid-19) which requires efforts to minimize it. The transportationcontrol policy is one of the most important components in preventing the spread of Covid19inordertomaintainpublic safety in maintaining the balance of the national economy.From this explanation, the background of the problem is First, how to control transportationduring the Idul Fitri homecoming period 1441 H based on PERMENHUB Number PM 25of 2020. Second, how is the Maqashid Syariah review of the Regulation of the Minister ofTransportation Number PM 25 of 2020. The research method used in this research is Library Research with the source ofinformation from library materials, data collection techniques through written work in theform of books, laws and regulations and materials needed to obtain information related tothe discussion. Then the data is analyzed using descriptive analysis method. Based on the results of the study, it is concluded as follows First, in the Regulationof the Minister of Transportation Number PM 25 of 2020, it is not permitted to usetransportation facilities, whether land, sea, air, railways, and for matters of an emergencynature. Second, the Maqashid Sharia theory explains its main purpose to protect religion,property, mind and soul. And the implementation of the Maqashid Sharia concept incontrolling transportation has fulfilled the benefits of the soul, religion and descendants ofthe community during the Eid al-Fitr homecoming period in 1441 H. Keywords: Maqashid Syariah, Transportation Control, Covid-19